Targeted deletion of numb and numblike in sensory neurons reveals their essential functions in axon arborization - Huang, Eric J. (Cold Spring Harbor Laboratory Press, 2005)
Mouse Numb homologs antagonize Notch1 signaling pathways through largely unknown mechanisms. Here we demonstrate that conditional mouse mutants with deletion of numb and numblike in developing sensory ganglia show a severe reduction in axonal arborization in afferent fibers, but no deficit in neurogenesis. Consistent with these results, expression of Cre recombinase in sensory neurons from numb conditional mutants results in reduced endocytosis, a significant increase in nuclear Notch1, and severe reductions in axon branch points and total axon length. Conversely, overexpression of Numb, but not mutant Numb lacking α-adaptin-interacting domain, leads to accumulation of Notch1 in markedly enlarged endocytic–lysosomal vesicles, reduced nuclear Notch1, and dramatic increases in axonal length and branch points. Taken together, our data provide evidence for previously unidentified functions of Numb and Numblike in sensory axon arborization by regulating Notch1 via the endocytic–lysosomal pathways.